The garrison of Kamianets-Podilskyi until the end of the 16th century - Hański, Oleg (City and War, 2021)
In the Early Modern Age, the fortress town of Kamianets-Podilskyi could boast not only with favorable natural conditions for defense, but also with well-placed fortifications. However, history is being made by people, not the rocks, and ultimately the security of the town depended on the „people of war” who protected the civilians. Being a strategic fortress situated on the intersection of trade routes, Kamianets-Podilskyi controlled the southern border of the Kingdom of Poland and was constantly endangered by Tatar, Moldavian and Turkish attacks. Therefore, it required the deployment of permanent garrison troops consisting of infantry for the defense of the castle walls, guarding and policing functions; artillery for intimidation of the enemy and inflicting casualties; and cavalry for conducting reconnaissance, controlling the roads and carrying out the sorties.